Intensive care unit prophylaxis and its outcome in a rural tertiary care hospital: an observational study - Ananth, P. Vijai; Bouddh, Surendra Kumar (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Intensive Care Unit is used to treat patients closer to their beds, in order to observe them more as distinct people to almost all the critically-ill patients. Methods: One hundred admitted patients in the ICU, 25 each sets of the patients observed their prophylactic management to prevent stress ulcer, pressure ulcer, UTI and chest infection, observations noted for the 7 days, directly by seeing and by cross-checked patient’s case-sheets. Results: There were 2 (8%) patients developed stress ulcer, 1 (4%) Catheter associated bacteriuria, 2 (8%) patients grade II pressure ulcer, and 5 (20%) patient’s done endotracheal intubation. All these 5 (20%) report of sputum culture found Ps. Aeruginosa, Klebsiella sensitive for Ceftriaxone + Sulbactum. The standard nursing care done by the on duty nursing staffs, i.e., no one given Ryle’s tube feeding for the stress ulcer cases, advised soft, palatable, non-spicy oral diet, Pressure ulcer’s 8% patients shifted on the air-bed mattress, ulcer’s cleaned with normal water soaked soft-napkin and applied sterile pad compressed dressing locally. For the ventilator in-situ patient’s, endotracheal tube cleaned 8-12 times within 12 hours. The Inbuilt Ventilator tube cleaned, and its filter changed and kept ready by the following standard aseptic precaution before using the ventilator. The chest physiotherapy was done by the chest medicine specialist of the all 5 ventilated patients. Prophylactic medication provided, i.e., Injection Pantoprazole 40mg once daily, Injection Ciprofloxacin 400mg twice daily, and Injection Inj. Ceftriaxone + Sulbactum gm 12 hourly interval administered daily. Conclusions: Standard nursing care was prime intervention as an Intensive Care Unit Prophylaxis along with Injection Pantoprazole 40mg once daily provided to prevent stress ulcer. Injection Ciprofloxacin 400mg twice daily provided to prevent Catheter Associated Bacteriuria. Injection Ceftriaxone + Sulbactum 1gm 12 hourly provided to prevent Ventilator Associate Pneumonia and pressure ulcer. Injection Ceftriaxone + Sulbactum 1gm 12 hourly interval. Intensive Care Unit’s Prophylactic measures helped to prevent further complication and reduced morbidity.